UPAYA HUKUM TERHADAP SURAT KEPUTUSAN MENTERI HUKUM DAN HAK ASASI MANUSIA TENTANG PENETAPAN PARTAI POLITIK (STUDI PERSELISIHAN KEPENGURUSAN PARTAI GOLKAR): Aryo Wirro Bimo Herdianto - admin, admin (Reformasi Hukum, 2018)
The Ministry of Law and HAM is authorized to execute Administrative Law. As set forth in Article 4 paragraphs 1-4 of Law No. 2 of 2011 on changes to Law No. 2 of 2008 on the Political Party which reads: “(1) The Ministry receives the registration and research and / or verification of equipment and truth as referred to in Article 2 and Article 3 paragraph (2); (2) The review and/or verification as referred to in paragraph (1) shall be undertaken at least 45 (forty-five) days after receipt of the complete requirements document; (3) The endorsement of the Political Party into a Legal Entity is made with the decision of the Minister at least 15 (fifteen) days after the end of the research and / or verification process; (4) The Minister's decision on endorsement of the Political Party as referred to in paragraph (3) shall be announced in the State of the Republic of Indonesia. However, the fact that Kemenkumham did not carry out its duties in accordance with Law No. 2 of 2011 on changes to Law No. 2 of 2008 on the Political Party. In the case of the Golkar party dispute, the government intervened in the ruling Golkar party, as the Decree issued by the Minister of Justice and HAM had no clear legal basis. Decree issued by the Minister of Justice and Human Rights confirming the ruling of the Laksono golkar party on the basis of the judgment of the Golkar party Court. While the Golkar Party Court itself, as the Internal Authority dealing with the case of the Golkar Party's dispute, has not ruled that the ruling of the Laksono Supreme Court is legitimate, but the content of the verdict is that the Golkar Party Court has not endorsed both (Laksono and Aburizal Bakrie's stronghold) due to differences of opinion and disagreements between the Golkar Party court and ordered that the case be brought to the State Court.